(untitled) (Al-Academy, 2020)
Shapes have differed in terms of their temporality, tools, technical variations, aesthetic functions and dimensions. The beginnings started with manual primitive techniques that have played an a significant artistic role in the ancient civilizations, then developed with the technological development and the digital technologies that encompassed various programs and specialist means in the graphic design, so that its visual outputs in the textbook that is considered a communication means that has an effect and attracts the recipient. That is what made the researcher search and investigate this topic describing the research problem as follows: What are the shapes as alternatives to the words in the design of the textbook? The research objective is to identify the shapes in the design of the textbook (the book of reading issued by the directorate of curricula in the ministry of education). The second chapter is dedicated to the theoretical framework which consists of the following sections. The first section (the concept of shape in the design), the artistic styles in employing shapes. The second section (the semiotic dimension for employing the typographical shapes in designing the textbook, the expressive-communicative dimension for employing the shapes). The researcher then dealt with the most important indicators the resulted from the theoretical framework. The third chapter consists of the research procedures, then the analysis of samples. The two researchers analyzed (5) models according to the axes derived from the indicators concluded from the theoretical framework. The fourth chapter is dedicated for presenting and discussing the results as follows: 1- The use of technology in employing the shapes in designing and writing of books and educational curricula led to promoting scientific material that is linked to the essence of the design process in terms of the recipient’s visual communication. 2- Shapes have not been employed as a substitute to the word rather as an alternative, in most of the pages and that has appeared in all the samples. As for the conclusions, it included a group: the book pages included shapes of various sizes and colors. Thus the primary school textbooks depend on shapes of various sizes and forms and that has a positive effect on the book aesthetics and the level of influence of the shapes on students (the recipient).